The Amelioration of BOD and COD Levels in Tofu Industry Liquid Waste by the Extracts of Moringa Seeds (moringa oleifera L.) and Activated Carbon of the Corn Cob (Zea mays L.) - Nurhadyati; Bibiana D. Tawa; Febri O. Nitbani (Journal of Applied Chemical Science, 2013)
There has been conducted a research to measure effectiveness of moringa seeds (moringa oleifera L) extract as biokoagulan and the activated carbon of corn cob (Zea mays, L) as adsorbent to ameliorate the chemical oxygen demand (COD) and biochemical oxygen demand (BOD) contents in tofu industry liquid waste. The used metods were, first method, the coagulation-floculation using moringa seed extract in various concentrations of 5000, 5200, and 5400 ppm, and the activated carbon of corn cob at concentration of 26.67 ppm and the second, the combination of coagulation/floculation with adsorption method. The results showed that the initial values of the COD and BOD of the tofu liquid waste were 1048.8 mg/L and dan 201.78 mg/L, respectively. The separated koagulation-floculation process provided maximum concentration of moringa seed extract was 5200 ppm and able to reduce COD and BOD levels respectively up to 555.07 and 161,68mg/L, while using 26.67 ppm of corn cob activated carbon could reduce the COD and BOD levels respectively up to512.13 and 115.42 mg/L; whereas the combination of coagulation/floculation-adsorption method utilizing 5200 ppm of biocoagulan and 26.67 ppm of the activated carbon yielded those COD and BOD levels respectively up to 272.93 and 73.07 mg/L. Referring to the SNI standard, these COD and BOD values meet the demand quality standard required. Both moringa seed extract and the corn cob activated carbon are prospective material to maintain COD and BOD levels of water flowing from the tofu industry.